Bioavailability of petroleum hydrocarbons to mangrove osyter (crassostrea belcheri G.B. Sowerby) from sediment in mangrove ecosystems of West Coast of Peninsular Malaysia - Vaezzadeh, Vahab (2015)
West coast of Peninsular Malaysia which faces to the Strait of Malacca has gone through rapid industrialization and urbanization and is susceptible to both sea-based and land-based petroleum pollution. Bioavailable petroleum hydrocarbons (PHC) can be toxic to aquatic organisms and pass along the food chain to higher levels, including humans. Consequently, a clear understanding of distribution and sources of PHC is of high importance in the region. Surface sediment samples and mangrove oyster (Crassostrea belcheri) were collected from five locations including the Merbok River, Prai River, Klang River, Muar River and Pulau Merambong in west coast of Peninsular Malaysia and investigated for the levels of PHC. Normal alkanes (n-alkanes), hopanes and polycyclic aromatic hydrocarbons (PAHs) fractions were extracted through soxhlet extraction, first step and second step column chromatography and injected to gas chromatography-mass spectrometry (GC-MS) for analysis. The total concentrations of n-alkanes ranged between 33697 and 290471 ng.g-1 dry weight (dw) in the sediments. The concentrations of n-alkanes in the sediments collected from different stations are in the order: Klang River > Prai River > Pulau Merambong > Merbok River > Muar River. Petroleum origin n-alkanes were predominant in the lower parts of the estuaries, while higher plant origin n-alkanes were predominant in the upper parts of the Rivers. Concentrations of nalkanes in the oysters ranged between 56661 to 262515 ng.g-1dw. The concentrations of nalkanes in the oysters from different stations are in the order: Klang River > Prai River > Merbok River > Pulau Merambong > Muar River. Low molecular weight (LMW) n-alkanes were more predominant in the oysters. Hopanes diagnostic ratios revealed used crankcase oil as the main source of hopanes in the sediment as well as in the oysters in the majority of sampling locations. The concentrations of total PAHs ranged between151and 4973 ng.g-1 dw in the sediments. The concentrations of PAHs in the sediments from various sampling stations are in the order: Klang River > Prai River > Merbok River > Muar River > Pulau Merambong. A predominance of pyrogenic source PAHs were detected in the sediments. The concentrations of PAHs in the oysters ranged from 309 to 2225 ng.g-1 dw. The concentrations of PAHs in the oysters from various stations follow the order: Klang River > Prai River > Merbok River > Pulau Merambong > Muar River. PAHs in the oysters were detected to be from mixed petrogenic and pyrogenic sources. A predominance of 2-3 ring PAHs was detected over 4 ring PAHs and 5-6 ring PAHs in the oysters. Significant correlations (p<0.05) were found between n-alkanes, hopanes and HMW PAHs in the sediments and oysters indicating that PHC body burden of the oysters is responsive to changes of PHC in the sediments. Moreover, biota accumulation factors (BAFs) of approaching or exceeding one were calculated for PHC in the majority of sampling locations, especially for LMW PHC indicating the ability of mangrove oyster to accumulate high levels of PHC. Overall, this study indicates that mangrove oyster (Crassostrea belcheri) can be a good biomonitor, especially for LMW PHC.